I Medici e l’incisione: Le origini della collezione di stampe degli Uffizi - Baroni, A. (Utrecht University, 2008)
This research focusses on the origins of the print collection of the Medici family, from the reign of Grand Duke Cosimo I to the extinction of the Medici dynasty with the death of the Elettrice Palatina Anna Maria Luisa de’ Medici in 1742. After the investiture of Grand Duke Pietro Leopoldo of Lorraine other large groups of prints were added to the collections, notably between 1769 and 1783, when Giuseppe Pelli Bencivenni compiled the first catalog of the Gabinetto dei Disegni e Stampe. A conspicuous part of the prints that are now kept in the Uffizi originate from the personal collections of the Grand Dukes and Princes of the Medici family. The reconstruction of the history of the print collection of the Uffizi is therefore partly based on a the parallel and comparative analysis of the archival records of the Guardaroba Medicea (Archivio di Stato Firenze) and those of the Galleria degli Uffizi, kept in the library of the museum and in the Archivio Storico delle Gallerie Fiorentine. The written sources also contain valuable references to the use and re-use of engraved plates under close control of the Guardaroba Generale until 1769-1772, when this part of the Medici collection was dispersed. My research also aims at the careful comparison between what can be found in the archival sources and the “physical” and “archeological” evidence of the print collections of the Uffizi in its present form. This allowed for the specific identification of prints that were once belonged to the Medici collections. Because of the lack of exhaustive and detailed archival references regarding the actual purchase of prints, the acquistion policy of the Medici family needs to be reconstructed by indirect ways : Part I: I broadened the scope of my research and propose to make a distinction between a) prints and engraved plates commissioned by the Medici within the network of (Florentine) printmakers, stampatori and print publishers, and b) “indirect” acquisition through diplomatic gifts, donations and dedications. Part II follows the same chronological pattern but focusses on the composition and gradual extension of the Medici print collection in the course of the centuries. With the help of these sources I have been able to identify albums, bound volumes etc. that securely stem from the Medici collections. In particular, I have been able to trace a part of the five volumes of prints that were assembled before 1625, known to have been in the possession of Cardinal Leopoldo de’ Medici, but possibly assembled by Ferdinando I. I finally identified the prints stemming from the collections of the Gran Principe Ferdinando, recorded after his death in 1713, as well as the ones from the collection of the Elettrice Palatina Anna Maria Luisa de’ Medici. Part III provides a complete and critical transcription of the archival documents, with many footnotes and specific references to the prints as they are actually kept in the museum’s collection. It comprises the catalog of the so-called “Volumi di Stampe”, the acquistion of which seems to be related to the old Medici collection.
Keywords: Letteren; Print collection of the Medici at Uffizi Gallery